Upper Limb Orthoses: Integrating Topology Optimization and 3D Printing for Custom Fit and Function - Stefanos Voulgaris; Charoula Kousiatza; George Kazakis; Konstantinos-Iason Ypsilantis; Dimitrios Galanis; Chara Ch. Mitropoulou; Maria Gkara; Stelios K. Georgantzinos; Konstantinos Soultanis; Nikos D. Lagaros (Applied Sciences)
Customized wrist splints, particularly for upper extremity orthoses like wrist support braces, are commonly used across numerous clinical scenarios. However, the traditional process for producing personalized wrist splints is largely manual and highly dependent on the expertise of orthopedic specialists. This experience-based approach often leads to suboptimal outcomes, necessitating further refinement of the designs. Recent advancements in Additive Manufacturing (AM) have brought significant innovation to various industries, including orthopedics. This study aims to present a comprehensive methodology that integrates advanced design tools, like 3D Scanning, with digital manufacturing techniques to produce tailored wrist splints. The produced hand brace aims to offer enhanced mechanical performance and comfort by precisely fitting an individual’s anatomy while minimizing material usage and weight. To achieve optimal design efficiency, the study explores the application of a topology optimization (TO) approach for design, while the manufacturing process utilizes Fused Deposition Modeling (FDM), an evolving technology within the additive manufacturing (AM) sector.